RANGKIANG AS A MODEL OF PLANNING AND RISK MANAGEMENT IN ISLAMIC ECONOMICS - Gilang Ahdi Ramadhan; Rizal Fahlefi; Ahmad Lutfi (RADJA PUBLIKA, 2025)
This study aims to examine the rangkiang system in Minangkabau culture as a conceptual model of family economic planning and risk management from an Islamic economic perspective. Using a Systematic Literature Review (SLR) method, the study analyzes various scholarly sources related to Islamic economics, family resilience, local wisdom, and Minangkabau adat philosophy, integrated with the principles of maqāṣid al-sharī‘ah. The findings reveal that the rangkiang system comprising Rangkiang Si Bayau-Bayau, Si Tangguang Lapa, and Rangkiang Kaciak reflects three core dimensions of Islamic economics: just and prudent consumption planning (qanā‘ah and tadbīr al-māl), social risk mitigation (iḥtiyāṭ and ta‘āwun), and intergenerational economic resilience (ḥifẓ al-nasl and ḥifẓ al-māl). The integration of Minangkabau customary values with Islamic teachings forms an indigenous Islamic economic system one that emerges from local cultural practices while remaining grounded in maqāṣid al-sharī‘ah. This study affirms that the Rangkiang Syariah Model can serve as a new paradigm in the development of applied Islamic economics based on local wisdom, strengthening Muslim family economic resilience and enriching the body of contextual Islamic economic theory in Indonesia.